Subjective career success of young people with learning disabilities in VET - Hofmann, Claudia; Häfeli, Kurt (Swiss Journal of Educational Research, 2018)
For young people with learning disabilities career start is often difficult. As measured by objective criteria (salary, position) they are also less successful in their professional life. But what’s about their subjective view of career success at the beginning of their career and which factors are influencing it? In a study (2006-2011) 525 trainees in a basic training with Federal VET Certificate and 183 trainees of a VET elementary training program of four branches were questioned at the end of their training. Results show that subjective career success is particularly related to personality, work features and training conditions, especially those at the company. Socio-demographic characteristics and school background are less important.